Needs Assessment for Developing a Learning Management System (LMS) to Improve Student Learning Outcomes in Computer Subject IN YEMENI SECONDARY SCHOOLS (SAMA ALYEMEN SCHOOL) IN SANA'A: A Case Study - Hanan Al-Hakimi; Sunardi Sunardi; Triana Rejekiningsih (International Journal of Science and Applied Science: Conference Series, 2024)
This case study investigated the development and implementation of a Learning Management System (LMS) Limit to Need Assessment only at Sama Alyemen School in Sana'a, Yemen, with the aim of enhancing student learning outcomes in the computer subject. The research identified the specific needs and challenges faced by the school, including inadequate technological infrastructure, low digital literacy, and varying levels of stakeholder engagement. By employing a mixed-method approach, combining quantitative surveys and qualitative interviews, the study highlighted critical gaps and provided recommendations for a phased LMS implementation. The respondents in this study consisted of three key groups: teachers, students, and administrative staff at Sama Alyemen School. They were 39 people, 30 students, 5 teachers, and 4 administrative .The findings emphasized the importance of infrastructure upgrades, digital literacy training, and stakeholder involvement to ensure the successful adoption of the LMS and to create a more personalized, engaging, and effective learning environment for students.